DEVELOPMENT OF REFLEXIVE COMPETENCE WITH THE HELP OF THE PROJECT METHOD IN ENGLISH LANGUAGE TEACHING FOR STUDENTS OF THE SPECIALTY “INFORMATION SYSTEMS AND TECHNOLOGIES” - Shvaikina, Nina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The development of reflexive competence and the process of evaluating the results becomes a prerequisite for the formation of each student as a thinking, sociable and socially active person. Therefore, from the huge number of different pedagogical technologies used in universities, it is necessary to choose one that more contributes to the development of these qualities. We believe that this technology is project-learning technology by which the students learn to analyze and evaluate themselves, other participants in interaction and joint activities. We believe that the use of project learning technology in the form of the web-quest in the lesson contributes to the development of the ability to reflect. The problem of research is the optimization of ways to form reflexive competence through project training at English lessons. The purpose of the study: to form a reflexive competence using the method of projects in English lessons. Object of study: process of reflexive competence formation in students. The subject of the study: the use of project training technology in the formation of reflexive competence in students of specialty “Information systems and technologies”. Experimental work was carried out in control and experimental groups among students of the above mentioned specialty. A total of 30 students participated in the experiment. The experimental and control group was an equal number of students - 15 people.